Reflectance of Jezero Crater Floor: 1. Data Processing and Calibration of the Infrared Spectrometer (IRS) on SuperCam. Issue 1 (4th January 2023) - Royer, C.; Fouchet, T.; Mandon, L.; Montmessin, F.; Poulet, F.; Forni, O.; Johnson, J. R.; Legett, C.; Le Mouélic, S.; Gasnault, O.; Quantin‐Nataf, C.; Beck, P.; et al.
Abstract: The Perseverance rover, Mars 2020 mission, landed on the surface of the Jezero crater, on 18 February 2021. This Martian crater is suspected to have hosted a paleolake as evidenced by the numerous detections of aqueously altered phases and thus is a promising candidate for the search for past Martian life. The SuperCam instrument, a collaboration by a consortium of American and European laboratories, plays a leading role in this investigation, thanks to its highly versatile payload providing rapid, synergistic, fine‐scale mineralogy, chemistry, and color imaging. After its landing, the first measurements of Martian targets with the infrared spectrometer of SuperCam (IRS) showed new instrumental behaviors that had to be characterized and calibrated to derive unbiased science data. The IRS radiometric response has thus been calibrated using periodic observations of the Aluwhite SuperCam Calibration Target (SCCT). Parasitic effects were understood and mitigated, and the instrumental dark and noise are characterized and modeled. The reflectance calibrated data products, provided periodically on the NASA Planetary Data System, are corrected for the main instrumental features. This radiometric calibration allowed us to study the 2.5 μm absorption band, which has been discovered in the Séítah unit and is associated with phyllosilicates‐carbonates mixtures. Plain Language Summary: This paper is an instrumental investigation of the infrared spectrometer (IRS) portion of the SuperCam instrument on the Mars Science Laboratory Perseverance rover. Work performed prior to and during flight operations enabled the derivation of a proper instrumental response suitable for calibration of infrared point spectra of rocks and soils observed along the rover traverse. The paper describes development of a full data reduction pipeline in which the radiometric response, sensitivity of the IRS electronic board to temperature, and electromagnetic interference artifacts were removed. A companion paper (Mandon et al., 2022, https://doi.org/10.1029/2022JE007450 ) investigates the IRS data set through Sol 379 in more detail. Here, we specifically explore the 2.5 μm band attributed to carbonates in Séítah unit's phyllosilicate‐carbonates mixtures. We found that such mixtures likely have a low carbonate content, which may indicate low amounts of chemical alteration or an alteration by a carbon‐poor fluid. Key Points: The infrared spectrometer of SuperCam on Perseverance has been successfully flight calibrated using the onboard calibration targets Calibration permitted to study the most challenging long wavelengths and thus to discover an absorption band at 2.5 μm Study of the 2.3 and 2.5 μm absorption bands showed the Séitah unit has variable clay and carbonate mixtures with low carbonate content